EXTRACELLULAR VESICLES OF STEM CELLS AS DIAGNOSTIC BIOMARKERS IN LIQUID BIOPSY OF SOMATIC AND ONCOLOGICAL DISEASES - Komarevtseva, I.O.; Balabanova, K.V.; Komarevtsev, V.M.; Chernykh, Yu.A.; Kalinin, I.V.; Rudenko, I.V.; Zhurba, O.A. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the prognostic value of extracellular vesicles (CD63 expression) in oncological and somatic diseases by liquid biopsies. To test our hypothesis, this case-control study consisted of the indicators of CD63 expression in the blood plasma of 20 healthy donors (control group); 18 patients with a positive diagnosis of COVID-19 according to PCR analysis; 33 patients with critical limb ischemia; 38 patients with renal cell carcinoma; 11 patients with uterine sarcoma. Extracellular vesicle was isolation from human plasma samples. Our studies have shown that the CD63 expression correlates with the progression of the deseases and lower survival. Thus, we performed this analysis to better understand the prognostic value of CD63 expression in somatic and oncologic diseases. Levels of circulating extracellular vesicles (CD63 expression) showed healthy donors group has the lowest mean value; uterine sarcoma group shows the highest mean value; groups with COVID-19 and renal cell cancer demonstrate similar mean values; group with critical limb ischemia shows an intermediate value. The results suggest that the CD63 can be a universal valuable marker in predicting complications and survival in somatic and oncological diseases.